2021
DOI: 10.1080/13602381.2021.1911402
|View full text |Cite
|
Sign up to set email alerts
|

Business models in the Asia-Pacific: dynamic balancing of multiple cultures, innovation and value creation

Abstract: Owing to the convergence of multiple cultures coupled with the unprecedented rapid development in the decades since the late 1990s, the value creation and innovation logic of Asia-Pacific business models (BMs) has been constantly altered by cultural heterogeneity and thus, have evolved into a more complex and diverse landscape relative to Western developed-economy BMs. Given that relevant issues remain under-researched, the main purpose of our collection is to fill this gap. We provide new insights into identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Innovation is the soul of a nation's progress, and it has become the research object of many scholars (Chin et al, 2021 ; Duan et al, 2021 , 2022 ), who study the internal mechanism of innovation from the perspectives of knowledge hiding, strategic risks, and Asia-Pacific business models. Liu and Shi ( 2009 ) defined employees' innovative behavior as the process of generating, introducing, and applying beneficial novel ideas or things in organizational activities, including forming or developing new ideas or technologies, changing the existing management procedures to improve work efficiency, etc.…”
Section: Theory and Modelmentioning
confidence: 99%
“…Innovation is the soul of a nation's progress, and it has become the research object of many scholars (Chin et al, 2021 ; Duan et al, 2021 , 2022 ), who study the internal mechanism of innovation from the perspectives of knowledge hiding, strategic risks, and Asia-Pacific business models. Liu and Shi ( 2009 ) defined employees' innovative behavior as the process of generating, introducing, and applying beneficial novel ideas or things in organizational activities, including forming or developing new ideas or technologies, changing the existing management procedures to improve work efficiency, etc.…”
Section: Theory and Modelmentioning
confidence: 99%
“…Previous research has identified numerous factors that influence the KSB of individuals in different context, for instance, technologies (Hislop, 2013) and relevant tools used, motivation, working environment, organizational culture (Chin et al, 2021a;DeLong and Fahey, 2000;Kankanhalli et al, 2005), personal values and self-identities (Bock et al, 2005), national culture (Chin et al, 2021b(Chin et al, , 2021c and trust (Akhavan et al, 2015;Jarrah and Alkhazaleh, 2020;Wasko and Faraj, 2000), however, most of these studies focus on the organizations in the private sector.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…To understand variation in the performance of innovating subjects in terms of the reciprocal behaviors of subgroups within their networks, scholars have focused on knowledge flow ( Duan et al, 2021a , 2022 ), resource sharing ( Lacerda and van den Bergh, 2020 ) and value creation ( Chin et al, 2021 ) among other variables. However, such research has tended to overlook the importance of heterogeneous reciprocity behaviors that are rooted in psychological factors.…”
Section: Introductionmentioning
confidence: 99%